2022
DOI: 10.3390/curroncol29110681
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-2-Altered Urothelial Carcinoma: Clinical and Genomic Features

Abstract: Background: Hypoxia is recognized as a key feature of cancer growth and is involved in various cellular processes, including proliferation, angiogenesis, and immune surveillance. Besides hypoxia-inducible factor 1-alpha (HIF-1α), which is the main mediator of hypoxia effects and can also be activated under normoxic conditions, little is known about its counterpart, HIF-2. This study focused on investigating the clinical and molecular landscape of HIF-2-altered urothelial carcinoma (UC). Methods: Publicly avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The correlation between HIF and VEGF, similar to our results, was also shown by Yin, who even considered the increase in angiogenesis to be a protective factor for the fetus, and the level of HIF is a prognostic indicator of CHD(16). Hypoxia-inducible factor (HIF) is the response to low oxygen supply in the body by premetazoans and is a factor that enables angiogenesis and fetal growth during the embryonic period and even in tumors by controlling gene transcription pathways (44,45). Angiogenesis stimulation plays an important role in this process, and in addition to brosis, in ammation, apoptosis and vascular calci cation, it is a highly important factor for the uterus and placenta (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between HIF and VEGF, similar to our results, was also shown by Yin, who even considered the increase in angiogenesis to be a protective factor for the fetus, and the level of HIF is a prognostic indicator of CHD(16). Hypoxia-inducible factor (HIF) is the response to low oxygen supply in the body by premetazoans and is a factor that enables angiogenesis and fetal growth during the embryonic period and even in tumors by controlling gene transcription pathways (44,45). Angiogenesis stimulation plays an important role in this process, and in addition to brosis, in ammation, apoptosis and vascular calci cation, it is a highly important factor for the uterus and placenta (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…CLIC3 has been found to be expressed in human placenta and fetal membranes ( Money et al, 2007 ), osteoblasts ( Brum et al, 2017 ), and various cancer cells ( Patel et al, 2019 ; Chen et al, 2020 ; Kawai et al, 2020 ). Its rich expression promotes immune evasion in cancer cells ( Vlachostergios et al, 2022 ). Addtionally, it was reported that in hepatitis B virus, CLIC3 promotes classical macrophage activation via the NF-κB pathway ( Liang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the ERK pathway and induction of C–C Motif Chemokine Ligand 2 (CCL2) are responsible for HSP47-induced angiogenesis Wang et al [ 73 ] Mettl3 BC cell lines T24 and UMUC-3 Transgenic mice Ablation of Mettl3 in bladder urothelial cells attenuates the oncogenesis and tumour angiogenesis of BC Abd El-Azeem, Ali and El-Shorbagy [ 74 ] GLUT4 BC tissue samples of radical cystectomies and TUR GLUT4 and fibroblast activation protein (FAP) expression is significantly associated with increased intratumour MVD and adverse clinicopathological factors Mori et al [ 75 ] VCAM-1 Preoperative plasma samples Elevated VCAM-1 is associated with aggressive BC. Preoperative VCAM-1 may serve as a biomarker to help identify patients likely to benefit from multimodal therapy Vlachostergios et al [ 76 ] HIF-2 Publicly available next-generation sequencing (NGS) data from muscle-invasive BC cell lines and patient tumour samples from the MSK/TCGA 2020 cohort were interrogated HIF-2-altered BC has an aggressive clinical and a distinct genomic and immunogenomic profile enriched in angiogenesis- and immune evasion-promoting genes Xia et al [ 77 ] PKM2 Genetically engineered mice BC cell lines RT112, 1376, UMUC3, and T24 and mouse BC cell line MBT2 PKM2 ablation in mouse urothelial cells and/or chemical inhibition of PKM2 reduces complex formation of PKM2 with STAT3, their nuclear translocation, and HIF1α- and VEGF-related angiogenesis Yang et al [ 78 ] Occludin Cell lines T24 and 5637. Human umbilical vein endothelial cells (EA.hy926) and 293 T BC tissue samples Occludin participates in the development of angiogenesis in BCs by activating the IL8/STAT3 pathway via STAT4 CEACAM1 , carcinoembryonic antigen-related cell adhesion molecule-1; DLL4 , delta-like 4; HAS-1 , hyaluronic acid synthase-1; HO-1 , haem oxygenase-1; AT1R , angiotensin II type 1 receptor; BCLA , bladder cancer–specific nuclear matrix protein; VEGFR , VEGF receptor; EDIL-3 , EGF like repeats and discoidin i like domains protein 3; FGFGR , fibroblast growth factor receptor; KLF5 , human Kruppel-like factor 5; BAI-,1 brain-sp...…”
Section: Alternate Factors Influencing Angiogenesis In Bladder Cancersmentioning
confidence: 99%